Variations In Gelatin And Pure Concentrations Of Cilembu Sweet Potato (Ipomoea batatas 'Cilembu') On The Chemical And Organoleptic Qualities Of Panna Cotta - Kurnia Hartati, Fadjar; Christian Theodorus, Fransiskus; Handarini, Kejora (Demeter: Journal of Farming and Agriculture, 2024)
Dessert that is currenlty a favorite dish in Indonesia is panna cotta. Panna cotta has a taste that tends to be sweet. chewy and soft texture. Panna cotta it means “cooked cream”. The basic ingedients for making panna cotta are cream mixed with sugar, gelatin and flavorings. Modifications can be made to Panna Cotta products by using additional Cilembu sweet potato puree. The aim of this research was to determine the effect of varying concentrations of gelatin and Cilembu sweet potato puree (Ipomoea batatas 'Cilembu') on the chemical and organoleptic quality of panna cotta. Another objective is to determine the right concentration of gelatin and cilembu sweet potato puree so that the best chemical and organoleptic quality of panna cotta is obtained. The research method that used in this research is a laboratory experimental quantitative method. The experimental design used in this research was a completely randomized design (CRD) which consisted of 1 factor, which was a combination of gelatin concentration treatment and Cilembu sweet potato puree consisting of 4 levels, namely: P2 = Gelatin 6g and Cilembu sweet potato puree 40g; P3 = Gelatin 6g and Cilembu Sweet Potato Puree 50g; P4 = Gelatin 7g and Cilembu Sweet Potato Puree 40g; P5 = Gelatin g and Cilembu Sweet Potato Puree 50g. Each treatment was repeated 4 times. The quality parameters observed were TPA, beta-carotene content and organoleptics which included colour, softness and taste